Learning website development with Django : a beginner's tutorial to building web applications, quickly and cleanly, with the Django application framework - Hourieh, Ayman (From technologies to solutions., 2008)
"This book will show you how to assemble Django's features and leverage its power to design, develop, and deploy a fully-featured website. It will walk you through the creation of an example web application, with lots of code. Each chapter will add new features to the site, and show what parts of Django to work on to build these features. This book has been specifically written for Python developers new to Django, and it's goal is to help you put together Django applications as quickly as possible. This book will give you clear, concise and, of course, practical guidance to take you from the basics of creating pages with Django through to learning the skills that will make you a Django developer to be reckoned with"--Resource description page